Endurance exercise has a negative impact on the onset of SOD1-G93A ALS in female mice and affects the entire skeletal muscle-motor neuron axis - Scaricamazza, Silvia; Nesci, Valentina; Salvatori, Illari; Fenili, Gianmarco; Rosina, Marco; Gloriani, Michela; Paronetto, Maria Paola; Madaro, Luca; Ferri, Alberto; Valle, Cristiana (Frontiers in Pharmacology, 2024)
Amyotrophic lateral sclerosis (ALS) is a fatal neuromuscular disease characterized by the degeneration of motor neurons that leads to muscle wasting and atrophy. Epidemiological and experimental evidence suggests a causal relationship between ALS and physical activity (PA). However, the impact of PA on motor neuron loss and sarcopenia is still debated probably because of the heterogeneity and intensities of proposed exercises. With this study, we aimed to clarify the effect of intense endurance exercise on the onset and progression of ALS in the SOD1-G93A mouse model.We randomly selected four groups of twelve 35-day-old female mice. SOD1-G93A and WT mice performed intense endurance training on a motorized treadmill for eight weeks, five days a week. During the training, we measured muscle strength, weight, and motor skills and compared them with the corresponding sedentary groups to define the disease onset. At the end of the eighth week, we analyzed the skeletal muscle-motor neuron axis by histological and molecular techniques.Intense endurance exercise anticipates the onset of the disease by one week (age of the onset: trained SOD1-G93A = 63.17 ± 2.25 days old; sedentary SOD1-G93A = 70.75 ± 2.45 days old). In SOD1-G93A mice, intense endurance exercise hastens the muscular switch to a more oxidative phenotype and worsens the denervation process by dismantling neuromuscular junctions in the tibialis anterior, enhancing the Wallerian degeneration in the sciatic nerve, and promoting the motor neuron loss in spinal cord. The training exacerbates neuroinflammation, causing immune cell infiltration in the sciatic nerve and a faster activation of astrocytes and microglia in the spinal cord.Intense endurance exercise, acting on skeletal muscles, worsens the pathological hallmarks of ALS such as denervation and neuroinflammation, brings the onset forward and accelerates progression of the disease. Our findings show the potentiality of skeletal muscle as target for both prognostic and therapeutic strategies; the preservation of skeletal muscle health by specific intervention could counteract the dying-back process and protect motor neurons from death The physiological characteristics and accessibility of skeletal muscle further enhance its appeal as a therapeutic target.